Effect of temperature on dissipation of [14C]-atrazine in a Brazilian soil - Mercedes de Andréa, Mara; Barifouse Matallo, Marcus; Yuri Tomita, Rúbia; Luchini, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 1997)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} @font-face {font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} a:link, span.MsoHyperlink {color:blue; text-decoration:underline; text-underline:single;} a:visited, span.MsoHyperlinkFollowed {color:purple; text-decoration:underline; text-underline:single;} p {margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The soil dissipation of the herbicide 14C-atrazine was studied by solvent extraction, thin-layer chromatography and radiometric techniques. Results here presented show it was directly proportional to the temperature increases. As the temperature increased, less extractable and more bound residues were detected. At the end of the incubation period, soil extracts contained mainly atrazine but also its hydroxyderivative at 10ºC and 20ºC, and more hydroxyatrazine than atrazine at 30ºC and 40ºC. The calculated Arrhenius activation energy was very high (96 kJ. mol-1) proving the predominance of chemical reactions favouring the hydrolysis. Exploratory analysis of the soil bound residues detected more than 90% as hydroxyatrazine, in all different temperature samples. Results suggest that in a soil with the characteristics of the soil here studied and at temperatures higher than 20ºC, atrazine would not be a free contaminant because chemical degradation would result only in the non-phytotoxic hydroxyatrazine, either as available or as bound residues.